Produtividade agroindustrial de genótipos RB de cana-de-açúcar da série 1993 em 3 regiões de cultivo do estado de Alagoas: estratificação de ambiente e análise de adaptabilidade e estabilidade - Silva, Wellyngton Chaves Monteiro da (2004)
The aim of this work was to analyse sugarcane RB (Republic of Brazil) clones as part of the series 93 of PMGCA-CECA/UFAL, to identify the best clones and evaluate the representativity of the areas where the essays were performed and so to subsidiary the recommendations of clones of the referred series which are in releasing process for commercial cultivation. The study was based on three competition essays using 23 sugarcane RB clones of the 93 series, and three varieties patterns (RB72454, RB83102 and SP79-1011). The essays were installed in 1998 in the following sugarcane mills: Caeté (UCA), in the city of São Miguel dos Campos-AL; Coruripe (UCO), in the city of Coruripe-AL; and Santo Antônio (USA), in the city of São Luis do Quitunde-AL. The selected environment were constituted of the combination of the number of cuts and places forming nine environments. The experimental design used was randomized block with four repetitions, being each formed by 104 replications (26 genotypes x 4 repetitions) each one of them composed of five furrows of 6 m in length, spaced as pattern used by the sugarcane mills. The evaluated caracters were PC (Pol of the cane), TCH (tons of cane for hectare) in three successive cuting (plant cane, first ratoon, and second ratoon). The initial statistic procedures were constituted of analysis of variance for each environment, followed by an analysis of evaluation of the significance of the interaction genotype x environment and the possibility to put together the environments where the genotypes did met show difference of performance. It was also estimated the parameters of stability and adaptability, according to methodology proposed by Eberhart and Russel (1966). Based on the obtained results, it was concluded that the best sugarcane RB clones of the 93 series were: RB931011, RB931530, RB931565, RB931566 and RB931611; and among the best clones, RB931011 and RB931566 had good environment adaptability, and those clones with ample adaptability were RB931530, RB931565 and RB931611. The best clones shown low stability in relation to their results.